If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1(x + -1y) + 3(y + -1x) = 0 (x * -1 + -1y * -1) + 3(y + -1x) = 0 (-1x + 1y) + 3(y + -1x) = 0 Reorder the terms: -1x + 1y + 3(-1x + y) = 0 -1x + 1y + (-1x * 3 + y * 3) = 0 -1x + 1y + (-3x + 3y) = 0 Reorder the terms: -1x + -3x + 1y + 3y = 0 Combine like terms: -1x + -3x = -4x -4x + 1y + 3y = 0 Combine like terms: 1y + 3y = 4y -4x + 4y = 0 Solving -4x + 4y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4y' to each side of the equation. -4x + 4y + -4y = 0 + -4y Combine like terms: 4y + -4y = 0 -4x + 0 = 0 + -4y -4x = 0 + -4y Remove the zero: -4x = -4y Divide each side by '-4'. x = y Simplifying x = y
| (2w+2b)(3w+5b)= | | (ln(4)^2/(2ln2)-(ln(2)^2)/(2ln2) | | 30=3x-9 | | 2lnx-6=0 | | -5=0.25(4t+20r)-8r | | 1-4x/2x-1 | | 8sinx+16=20 | | t(2+-5t+3t^2)=0 | | 8+3x=x | | n^2+4n+16=0 | | 15z-(-3x-10x)= | | 2x^2+28=1 | | 3x-5y=42 | | n^3-64=0 | | X-0.6x=12 | | h^2+6h+9= | | 3x^2-60x+400=0 | | 7a+4b=32 | | 3(2x-4y)-2(2x-5y)+2y= | | ln(4x+5)=ln(2x-1)+ln(3) | | x+(x+1)+(x+2)+(x+3)=66 | | 2x+96-0= | | 4y+3=14 | | 38x+5y= | | 4y+4x-xy=0 | | 2p^2-2p/7p-7= | | Sqrt[x]=30 | | x-4y-12=0 | | dx+x(lnx-lny-1)dy=0 | | x^2-2x=-1/2 | | 3x+3y=132 | | 20x-(7x-8)=47 |